The role of cations in the interactions between anionic N-heterocycles and SO2 - Chenchen Li (Nature Portfolio, 2018)
Abstract Our study shows that cation plays a more important role in the interactions between anionic N-heterocycles and SO2 than in the NHC-CO2 case. The adducts of NHC, SO2 and cation often exhibit multiple stable configurations with close energies rather than the only reported “CO2-sandwiched” planar NHC-CO2-cation structure. The structural diversity makes the models omitting cation inappropriate for predicting the SO2 capture products, which also leads to less clear trends of the cation effects than those observed in the CO2 case. The detailed cation effects are discussed in the text.